MANAJEMEN KURIKULUM BERBASIS PENDIDIKAN LIFE SKILL DI PONDOK PESANTREN PROGRESIF FATHIMAH AL AMIN - Mu'azzaz, Nisrin; Chamami, M. Rikza (CV. Lafadz Jaya, 2025)
This research is motivated by the lack of quality human resources (HR), so boarding schools need to produce graduates who are not only religious but also have broad competencies. The implementation of a curriculum based on life skills education in boarding schools is one of the efforts that boarding schools can make to produce quality graduates. Therefore, this research was conducted to find out how the management of life skill education-based curriculum. This research is classified as qualitative field research. The data sources in this study were obtained through interviews with the boarding school caregivers, extracurricular coaches, and students of Fathimah Al Amin Progressive Islamic Boarding School. In addition, observation and documentation were also carried out during data collection. Data analysis in this study was carried out by reducing data, presenting data, and drawing conclusions. The results showed that the Progressive Fatimah Al-Amin Islamic Boarding School had implemented comprehensive management in organizing a curriculum based on life skills education. This is evidenced by the existence of careful planning, effective organization, structured implementation, and continuous supervision so that the Progressive Fatimah Al-Amin Islamic Boarding School succeeds in creating a learning environment conducive to the development of santri competencies.